SPECIES DISTRIBUTION UPDATE OF MANSONIA BLANCHARD, 1901 MOSQUITOES (DIPTERA: CULICIDAE) IN INDONESIA WITH THE ILLUSTRATED KEY FOR FEMALE MOSQUITO - Sidiq Setyo Nugroho; Mujiyono Mujiyono; Fahmay Dwi Ayuningrum (BRIN Publishing (Penerbit BRIN), 2021)
Mansonia is a genus of mosquitoes of which several species are confirmed vectors of lymphatic filariasis. Many countries including Indonesia are still struggling to eliminate lymphatic filariasis. Report of the Mansonia mosquito diversity and its distribution is essential to develop the control strategies. Six of eight Mansonia species have been confirmed as lymphatic filariasis vectors in Indonesia. This paper aims to update the distribution of the Mansonia mosquito in Indonesia. Species distribution data were summarized from various literature regarding the Mansonia mosquito. The data is complemented by the results of the National Research on Disease Vector and Reservoir (Rikhus Vektora) results conducted by the National Institute of Health Research and Development (NIHRD) in 2015-2018. There were new distribution records for four species of Mansonia mosquitoes in Indonesia. Mansonia annulata Leicester, Ma. annulifera (Theobald), and Ma. indiana Edwards are now recorded distributed throughout the archipelago. Meanwhile, Ma. bonneae Edwards has a new distribution record in the Moluccas. The illustrated identification key for female Mansonia mosquitoes in Indonesia is provided in this paper.